Disinformation and manipulation of public opinion: a systematic review of astroturfing (2004-2024) - García-Estévez, Noelia (2025)
Purpose. This article presents a systematic review of the scientific literature on the phenomenon of astroturfing, with particular attention to its impact on digital communication and manipulation of public opinion. Online astroturfing, as a disinformation strategy, simulates an authentic grassroots movement when it is a false orchestrated campaign that erodes democratic deliberation. This research responds to the need to systematically study astroturfing campaigns, given the scarcity of reviews on the topic (Kovic et al., 2018; Zhang et al., 2013). Methodology. Based on the analysis of 28 studies published between 2004 and 2024 in international databases, the main definitions, theoretical and methodological approaches, thematic areas, and application contexts are examined. The analysis was conducted using an ad hoc form that allowed the collection of key information such as the object of study, employed methodology, definitions used, and conclusions of each work. Results and conclusions. The results reveal a notable conceptual dispersion and thematic concentration in political and digital contexts. Research gaps—regarding themes, methods, and contexts—are identified, and emerging lines for future research are proposed. Original contribution. This work provides a systematic overview of the current state of the field and contributes to consolidating the study of astroturfing within Social Sciences and Communication. It proposes a consensual definition of astroturfing and offers a solid foundation to guide future studies and develop practical interventions.